2013
DOI: 10.1016/j.molcel.2013.01.036
|View full text |Cite
|
Sign up to set email alerts
|

The E3 Ligase Parkin Maintains Mitochondrial Integrity by Increasing Linear Ubiquitination of NEMO

Abstract: Parkin, a RING-between-RING-type E3 ubiquitin ligase associated with Parkinson's disease, has a wide neuroprotective activity, preventing cell death in various stress paradigms. We identified a stress-protective pathway regulated by parkin that links NF-κB signaling and mitochondrial integrity via linear ubiquitination. Under cellular stress, parkin is recruited to the linear ubiquitin assembly complex and increases linear ubiquitination of NF-κB essential modulator (NEMO), which is essential for canonical NF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
163
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(172 citation statements)
references
References 34 publications
7
163
0
2
Order By: Relevance
“…In our studies, we found that, unlike the WT RBR domain, a mitochondrially- [44]. Another recent study reported a new function for Parkin showing that in response to cellular stress, Parkin is recruited to the linear ubiquitin chain assembly complex, and increases linear ubiquitylation of NEMO, a process that is critical for the activation of the NF-κB pathway [45]. Our finding that Parkin can associate with ubiquitin chains attached to substrates may provide an explanation for these observations.…”
Section: Parkin Binds K63-linked Ubiquitin Chainssupporting
confidence: 56%
“…In our studies, we found that, unlike the WT RBR domain, a mitochondrially- [44]. Another recent study reported a new function for Parkin showing that in response to cellular stress, Parkin is recruited to the linear ubiquitin chain assembly complex, and increases linear ubiquitylation of NEMO, a process that is critical for the activation of the NF-κB pathway [45]. Our finding that Parkin can associate with ubiquitin chains attached to substrates may provide an explanation for these observations.…”
Section: Parkin Binds K63-linked Ubiquitin Chainssupporting
confidence: 56%
“…Because previous studies have implicated single heterozygous mutations in PARK2 and PINK1 as possible risk factors for developing parkinsonism,51 we performed a comprehensive mutation analysis of both genes in our patients, but failed to identify pathogenic variants. Notably, a direct link was recently established between Parkin and OPA1, through linear ubiquitination of NF‐kB essential modulator, which upregulates the expression of OPA1, promoting mitochondrial integrity and protecting from stress‐induced cell death 52. Conversely, alterations in both mitochondrial morphology and ATP production caused by either Parkin or PINK1 loss of function can be rescued by overexpressing the mitochondrial fusion proteins MFN2 and OPA1 53.…”
Section: Discussionmentioning
confidence: 99%
“…The realization that these proteins are in a single pathway, with PINK1 acting upstream of Parkin to influence mitochondrial properties, was a critical step in uncovering the underlying pathological mechanisms of PD (5)(6)(7). This pathway can trigger the selective autophagy of damaged mitochondria, termed mitophagy (8,9), but additional cellular functions have also been indicated for PINK1 and Parkin (10)(11)(12)(13)(14)(15). Much, however, remains unclear about how the PINK1/Parkin pathway is regulated.…”
mentioning
confidence: 99%